Persepsi Petani Terhadap Inovasi Kopi Robusta Organik di Kabupaten Lampung Barat - Cindy Nur Rohma; Dewangga Nikmatullah; Serly Silviyanti Soepratikno; Tubagus Hasanuddin (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
Perceptions play a crucial role in the adoption of innovation, particularly in the context of organic farming practices. This study aimed to explore farmer perceptions and factors influencing their perceptions of organic coffee innovation in Robusta coffee cultivation in West Lampung Regency. The research was conducted from December 2022 to January 2023, with a sample of 59 respondents from three farmer groups: Ampera, Langgeng Mulyo, and Margo Rahayu. Using a questionnaire and non-parametric statistical analysis, including the Rank Spearman correlation test, the study found significant relationships between farmer knowledge, availability of capital, social interaction, and marketing with their perceptions of organic coffee innovation. However, land area, length of farming, and selling price did not show significant relationships. These findings highlight the importance of enhancing farmer knowledge and providing adequate capital support, facilitating social interactions, and improving marketing strategies to promote the adoption of organic Robusta coffee cultivation. The government's attention to market development and pricing mechanisms for organic Robusta coffee can further incentivize farmers to engage in this sustainable agricultural practice.